2015
DOI: 10.1016/j.chaos.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer network representation of membrane potential and cytosolic calcium concentration dynamics in beta cells

Abstract: a r t i c l e i n f o a b s t r a c tModern theory of networks has been recognized as a very successful methodological concept for the description and analysis of complex systems. However, some complex systems are more complex than others. For instance, several real-life systems are constituted by interdependent subsystems and their elements are subjected to different types of interactions that can also change with time. Recently, the multilayer network formalism has been proposed as a general theoretical fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Due to its advantageously-high sensitivity, [Ca 2+ ] i imaging is used most commonly [ 134 ] and was successfully employed to indicate the degree of synchronicity between beta cells in mouse [ 73 , 127 , 135 , 136 , 137 ] and human islets [ 83 , 103 , 138 , 139 , 140 , 141 , 142 ]. Recently, data on [Ca 2+ ] i dynamics in mice provided valuable novel insight into the physiology of beta cells [ 78 , 79 , 80 , 81 , 87 ]. However, since beta cell stimulus-secretion coupling is complex in the sense that it involves many additional steps upstream and downstream from changes in [Ca 2+ ] i , deducing the whole signaling from the input in the form of glucose and other nutrients to the output in the form of insulin secretion by analyzing changes in [Ca 2+ ] i only is not possible.…”
Section: Part I: Assessing Beta Cell Function Using Mp and [Ca mentioning
confidence: 99%
See 3 more Smart Citations
“…Due to its advantageously-high sensitivity, [Ca 2+ ] i imaging is used most commonly [ 134 ] and was successfully employed to indicate the degree of synchronicity between beta cells in mouse [ 73 , 127 , 135 , 136 , 137 ] and human islets [ 83 , 103 , 138 , 139 , 140 , 141 , 142 ]. Recently, data on [Ca 2+ ] i dynamics in mice provided valuable novel insight into the physiology of beta cells [ 78 , 79 , 80 , 81 , 87 ]. However, since beta cell stimulus-secretion coupling is complex in the sense that it involves many additional steps upstream and downstream from changes in [Ca 2+ ] i , deducing the whole signaling from the input in the form of glucose and other nutrients to the output in the form of insulin secretion by analyzing changes in [Ca 2+ ] i only is not possible.…”
Section: Part I: Assessing Beta Cell Function Using Mp and [Ca mentioning
confidence: 99%
“…Furthermore, in every cell, the increase in MP typically precedes the increase in [Ca 2+ ] i by >100 ms [ 86 ]. Finally, a multilayer network representation and analysis of the MP and [Ca 2+ ] i signal propagation assessed in mice by means of our double stain paradigm showed that the largest delays between the MP and the [Ca 2+ ] i signal are present in the most connected cells in the tissue [ 80 ]. This observation can be a consequence of various reasons that are principally related with the well-known heterogeneity of beta cells [ 60 , 65 ].…”
Section: Part I: Assessing Beta Cell Function Using Mp and [Ca mentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, multiplex networks (the sub-class of multi-layer networks where nodes are the same on all layers) found applications in technological [3][4][5], biological [6], and social systems [7,8], as well as in human brain, artificial intelligence and robotics [9,10]. Multiplex networks are furthermore useful tools for the analysis of climatological data, e.g.…”
Section: Introductionmentioning
confidence: 99%